Alveolar soft part sarcoma of tongue base — A rare presentation of a rare tumor - Raghunandhan, S. (Springer-Verlag, 2007)
Alveolar soft part sarcoma is a rare, aggressive malignancy of uncertain histologic origin and enigmatic clinical behaviour. It has a characteristic histopathological picture, with a propensity for vascular invasion and distant metastasis. We report a case of alveolar soft part sarcoma involving the tongue base in an adolescent female. She underwent laser assisted excision of the tongue base tumour followed by post-operative radiotherapy. The clinical presentation, histopathological picture, immunohistochemical & cytogenetic studies, radio-imaging, management protocols and prognosis of this tumor have been discussed.